ARABIC LANGUAGE LEARNING FOR QUR'AN MEMORISERS - Andi Nurizzah Aqilah; Agus Yasin (Lahjah Arabiyah : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2026)
Arabic language learning plays an important role in Islamic education, including in the context of Al-Qur'an memorisation programmes. However, Arabic language learning applied to Al-Qur'an memorisers is generally conducted in a generic manner and has not been designed according to the specific needs of the memorisation process. In fact, huffaz require a pedagogical approach that can support accuracy of pronunciation, strengthen memorisation retention, and facilitate recognition of language patterns in the text of the Al-Qur'an. This study aims to examine the urgency of developing Arabic language learning specifically designed for Qur’an memorizers as a supporting approach in the tahfiz process. This study uses a qualitative method with a library research approach through analysis of relevant literature on Arabic language learning and Qur’an memorisation. The results of the study indicate that Arabic language learning that is oriented towards Qur'anic vocabulary, recognition of sentence structure in verses, and contextual basic meaning is more relevant to the needs of huffaz than general Arabic language learning. Arabic language learning in this context is not intended to replace other disciplines of Qur’anic studies, but rather serves as a pedagogical foundation that supports the effectiveness and sustainability of Qur’an memorisation.